2011
DOI: 10.1002/cncr.25971
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of alternating mammography and magnetic resonance imaging for screening women with deleterious BRCA mutations at high risk of breast cancer

Abstract: BACKGROUND: Magnetic resonance imaging (MRI) has been used to supplement screening mammography and clinical breast examination (CBE) in women who are at high risk of developing breast cancer. In this study, the authors investigated the efficacy of alternating screening mammography and breast MRI every 6 months in women who had a genetically high risk of developing breast cancer. METHODS: A retrospective chart review was performed on all women who were seen in a high-risk breast cancer clinic from 1997 to 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 87 publications
2
48
0
2
Order By: Relevance
“…We agreed with Le-Petross et al [17] that the breast density is one of the most important factors limiting the sensitivity of mammography and that was encountered in six cases in our study. In our study the high specificity of mammography may be attributed to selection of cases unlike studies which evaluated general population and healthy women who undergo periodic screening.…”
Section: Discussionsupporting
confidence: 94%
“…We agreed with Le-Petross et al [17] that the breast density is one of the most important factors limiting the sensitivity of mammography and that was encountered in six cases in our study. In our study the high specificity of mammography may be attributed to selection of cases unlike studies which evaluated general population and healthy women who undergo periodic screening.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, bipartisan legislation that would set a minimum federal standard about breast density notification has been introduced in the Senate of United States Federal Government [51].Supplemental screening options include both hand-held and automated whole-breast ultrasound, magnetic resonance imaging (MRI), and a more recently introduced modality, digital breast to mosynthesis. These recent legislative movements, however, have brought up several issues [52]; first, no guidelines have been established as to which modality should be used as supplemental screening for women with dense breasts; second, although ultrasound and MRI have been evaluated as supplemental screening tools with relatively limited population [20,[53][54][55], evidence showing their effectiveness as supplemental screening for women with dense breasts is limited at this point [21]; third, supplemental screening examination leads to more false-positive results [20,21,56], which will result in an increase in needle biopsies with benign results; fourth, legislation regarding insurance coverage of supplemental modality is lagging behind breast density notification bills.…”
Section: Legislative Movement Regarding Breast Density In the United mentioning
confidence: 99%
“…Many studies have shown benefit in high-risk populations (> 20% lifetime risk). 28,[40][41][42][43][44][45] In 2008, Warner et al 46 performed a meta-analysis of 11 prospective studies that compared the sensitivity rates of annual screening mammography performed in conjunction with MRI and annual screening mammography alone. Their meta-analysis found an increase in sensitivity rate of 94% when mammography was combined with MRI as compared with a rate of 32% for mammography alone.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The results from studies show that the benefits of MRI typically outweigh the limitations among patients with an estimated lifetime risk of breast cancer of higher than 20%. 28,[40][41][42][43][44][45][46][47] As new data become available, additional indications may emerge. In the meantime, no clear indication exists for performing screening MRI in patients with dense breasts, and the recommended use of screening MRI in this population should be the same as that for the general population based on personal risk.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%